Determining fertilizer quantities required for wheat - Kresović Mirjana M.; Ličina V. (Journal of Agricultural Sciences (Belgrade), 2003)
In this experiment we used brown forest soil that has been used in long-term experiments, for 30 years, with increasing doses of introduced nitrogen fertilizer in variants. In order to determine the quantities of nitrogen fertilizer required for wheat, a calculation model has been applied. This calculation requires not only a reliable method for determining soil nitrogen availability (both the total and easily hydrolyzed nitrogen method were used), but also a reliable method for determining the coefficient of nitrogen utilization from soil as well as data on the coefficient of nitrogen utilization from fertilizer (Nani) for the added quantities of nitrogen fertilizer.